Malnutrition according to ESPEN consensus predicts hospitalizations and long-term mortality in rehabilitation patients with stable chronic obstructive pulmonary disease. Issue 5 (October 2019) - Marco, Ester; Sánchez-Rodríguez, Dolores; Dávalos-Yerovi, Vanesa N.; Duran, Xavier; Pascual, Eva M.; Muniesa, Josep M.; Rodríguez, Diego A.; Aguilera-Zubizarreta, Ana; Escalada, Ferran; Duarte, Esther
Summary: Background: Nutritional disorders are frequent in patients with chronic pulmonary obstructive disease (COPD) and have negative health impacts. This study aimed to explore the value of the European Society of Clinical Nutrition and Metabolism (ESPEN) definition of malnutrition (and/or its individual components) to predict hospitalizations and mortality at 2 years, and to determine the prevalence of malnutrition in COPD patients referred to pulmonary rehabilitation. Methods: The study was a prospective analysis of 118 patients with COPD free of exacerbations and/or hospital admissions in the previous two months. Main outcome variables were mortality, hospital admissions, and length of stay at 2-year follow-up; main covariates were malnutrition assessment according to the ESPEN definition and its components: unintentional weight loss, body mass index, and fat-free mass index (FFMI). Body composition was assessed by bioimpedance analysis. Kaplan-Meier survival curves and linear regression analyses were performed, adjusting for age and airflow obstruction as potential confounders. Results: The observed prevalence of malnutrition was 24.6%. Malnutrition was associated with increased mortality risk (HR = 3.9 [95% CI: 1.4–10.62]). FFMI was independently associated with increased mortality (HR = 17.0 [95% CI: 2.24–129.8]), which persisted after adjustment for age and lung function (adjusted HR = 13.0 [95% CI: 1.67–101.7]). Low age-related body mass index was associated with increased risk of hospital admissions. Conclusions: Malnutrition according to ESPEN criteria, highly prevalent in patients with stable COPD referred to pulmonary rehabilitation, was associated with 4 times greater mortality risk after 2 years. Low FFMI was associated with a 17-fold increase in mortality risk, suggesting independent predictive value. Highlights: The prevalence of malnutrition according to ESPEN criteria in patients with stable COPD was 24.6%. Malnutrition is associated with 3.9-fold increased risk of mortality at 2-year follow-up. Fat-free mass index was associated with 17 times greater risk of mortality, the highest factor of all ESPEN components. Low age-related body mass index was the only component associated with increased risk of hospital admissions.